A Review of the Methods Used in the Study of Creep Behavior of Fiber-Reinforced Composites and Future Developments - Mostafa Katouzian; Sorin Vlase (Applied Sciences)
This paper presents the main methods for analyzing the creep of fiber-reinforced composite materials used by researchers. Creep is a characteristic property of composites made of a fiber-reinforced matrix and determines the acceptability of some materials in various engineering applications. The paper attempts to update the works in the field with recent research and analyzes the main methods for modeling these types of materials, the calculation methods, and the results obtained by researchers. It thus provides a framework for researchers to choose the most appropriate calculation method for the specific application studied. The results that have already become classics, along with the results that have appeared recently and special cases, are critically presented in the paper. Future research directions are highlighted for the various methods described and for the field as a whole.